SIPEA: Web Application for Celia Sánchez Manduley Hospital in Manzanillo. - MustelierHechavarría, Antonio; Castro Dieguez, Fidel Enrique; Verdecia Cabrera, Alberto; Aliaga Benavides, Adriel Alejandro; Hechavarría Figueredo, Julio (Revista Cubana de Informática Médica)
Anemia is the most common blood disorder in the world, affecting millions of people yearly. It has multiple causes and jeopardizes development, growth and learning. Current tools provide non-hematologist doctors with just numbers. The present paper proposes a web application intended to provide doctors at Celia Sánchez Manduley Hospital in Manzanillo with a tool for determining the morphologic type of anemia, creating a list of possible causes, and also storing patient data in a database for future researches. As an information system, the website constitutes a powerful tool for the decision-making process, in particular, the diagnostic process, intended to provide more detailed information on anemia as well as to foster the information management at the hospital. For the application, HTML, CSS, JavaScript and PHP were used as languages; Apache as a web server; CodeIgniter as a PHP framework; MariaDB as a database management system; and Visual Studio Code as a development environment.